2019
DOI: 10.1080/19476337.2019.1695677
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of soluble protein, polypeptide production and functional properties of heat-denatured soybean meal by fermentation of Monascus purpureus 04093

Abstract: The aim of this study was to investigate the effect of fermentation parameters on heat-denatured soybean meal by Monascus purpureus 04093 on the soluble protein and polypeptide production and to evaluate the antioxidant activity and functional properties of the fermented products. The optimal fermentation parameters were obtained as follows: 11.25% soybean meal loaded in a 80 g/500 mL flask with 0.02 g/L Na 2 SO 4 at 28°C and pH 6.5 for 96 h. The soluble protein and polypeptide yield reached 290.9 ± 3.4 mg/g a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The observed decrease in soluble protein levels, which was accompanied by a significant increase in total protein content in Tre-treated seedlings, could be attributed to a change in their solubility due to Tre treatment. This suggestion is supported by the fact that the level of soluble protein is positively correlated with protein solubility (Afify et al 2012, Ma et al 2019, Ebert et al 2020. Therefore, the increase in total protein while the soluble protein decreased can be due to the role of Tre in reducing the solubility of proteins.…”
Section: Discussionmentioning
confidence: 95%
“…The observed decrease in soluble protein levels, which was accompanied by a significant increase in total protein content in Tre-treated seedlings, could be attributed to a change in their solubility due to Tre treatment. This suggestion is supported by the fact that the level of soluble protein is positively correlated with protein solubility (Afify et al 2012, Ma et al 2019, Ebert et al 2020. Therefore, the increase in total protein while the soluble protein decreased can be due to the role of Tre in reducing the solubility of proteins.…”
Section: Discussionmentioning
confidence: 95%
“…This approach not only facilitates its reuse but also generates economic benefits while mitigating its environmental footprint. 28 Red koji releases a variety of enzymes capable of breaking down microbial proteins. These enzymes effectively disintegrate the large, insoluble protein clusters found in soybean meal into smaller, soluble proteins and polypeptides.…”
Section: Carbon Sourcementioning
confidence: 99%
“…However, it harbors untapped potential as a substrate for red yeast fermentation. This approach not only facilitates its reuse but also generates economic benefits while mitigating its environmental footprint 28 . Red koji releases a variety of enzymes capable of breaking down microbial proteins.…”
Section: Fermentationmentioning
confidence: 99%
“…The FS diagram of HDPM shows that FS at pH 10 was significantly higher than at other pH values (p < 0.05). Ma and colleagues used Monascus purpureus to ferment heat-denatured soybean meal and measured changes in nutritional composition, antioxidant activities, and physicochemical properties of fermented soybean meal [51]. The results showed that the contents of polysaccharide and amino acids, antioxidant activities, emulsifying properties, and foaming abilities of the fermented heat-denatured soybean meal were significantly increased.…”
Section: Physicochemical Properties Of Fhdpm and Hdpmmentioning
confidence: 99%